Audit of a tuberculosis contact tracing clinic. Issue 6836 (9th May 1992) - Hussain, S. F.; Watura, R.; Cashman, B.; Campbell, I. A.; Evans, M. R.
Abstract : OBJECTIVE--To determine the efficiency of tuberculosis contact tracing in South Glamorgan 1987-9. DESIGN--Review of records of contact tracing clinic and of data from the Mycobacterium Reference Unit. The clinic's practice was compared with 1983 British Thoracic Society's recommendations. SETTING--Health authority tuberculosis control programme. MAIN OUTCOME MEASURES--Proportion of contacts screened, follow up attendance rates, number of secondary cases detected, and quality of record keeping. RESULTS--101 index patients and 611 contacts were identified. 596 (97.5%) contacts were screened, of whom 139 should not have been. Of 356 contacts requiring a Heaf test, 237 were tested, seven refused the test, and 112 had chest radiography without a Heaf test. 95 contacts were unnecessarily tested. 87 contacts had chest radiography unnecessarily and seven should have had radiography but did not. 34 contacts were given follow up appointments inappropriately and seven were overlooked for follow up. Tuberculosis was diagnosed in five asymptomatic contacts, all at initial screening and all close contacts of index patients with pulmonary disease. CONCLUSION--Inadequacy of data, non-adherence to contact tracing guidelines, and failure to define the term highly infectious index case resulted in many contacts being unnecessarily screened or followed up. IMPLICATIONS--The efficiency of tracing contacts would be improved by specifying smear results and ethnic origin of the index case on the notification form, clearly classifying contacts as close or causal, and clearly defining the term highly infectious.